Patient satisfaction toward aesthetic and functional outcomes: a comparative study of acrylic vs. cobalt-chrome removable partial dentures - Ahmad, Norfaezah; Harun, Siti Khadijah; Habit Mustafa, Syarifah Anisah; Wan Nik, Wan Noor Nazayan; Mohd Ibrahim, Mohamad Shafiq (IIUM Journal of Orofacial and Health Sciences, 2025)
Removable partial dentures (RPD) are effective prostheses for restoring both function and aesthetics following tooth loss. Patient satisfaction with RPD functional and aesthetic outcomes is critical in determining the success of RPD therapy. This study aimed to evaluate and compare patient satisfaction with the function and aesthetics of acrylic and cobalt chrome (Co-Cr) RPD and identify factors affecting patients' satisfaction with RPD. Ninety-one patients who received RPD from undergraduate dental students from Kulliyyah of Dentistry (KOD), IIUM, participated in this study. The number of RPD issued for these patients was 150 units, with 121 (80.7%) acrylic and 29 (19.3%) Co-Cr RPD. Patients completed validated questionnaires consisting of four sections: demographics information, patient satisfaction towards the function of RPD, patient satisfaction towards aesthetics of RPD and patient perception towards retention and stability of RPD. Data analysis was conducted using Microsoft Excel 2016 and SPSS version 25. Mann-Whitney U tests were used to analyse and compare patient satisfaction levels of RPD. A chi-square test was used to examine patients’ perceptions of retention and stability of their RPD. Analysis was set as p<0.05 with a 95% confidence interval as statistically significant. The majority of patients reported greater functional and aesthetic satisfaction with acrylic removable partial dentures (RPDs) compared to cobalt-chromium (Co-Cr) RPDs. There was no significant relationship between patient satisfaction with retention and stability of RPD. In conclusion, acrylic RPDs were perceived to be superior to Co-Cr RPDs, and patient satisfaction was not influenced by the retention or stability of the RPDs.